Experimental Study: The Effect of Public Speaking Skills on the Quality of Student Group Presentations in the History of Religion Course, Academic Year 2025-2026 (Al-Ilmu, 2025)
This study aims to determine the effect of public speaking skills on the quality of group presentations among students in the History of Religion course. The background of this research is the low ability of students to deliver presentation material effectively, even though they have mastered the content. The study used an experimental method with a pre-test post-test control group design. The sample consisted of 20 students divided into two groups: an experimental group given public speaking training and a control group without training. Data were collected through observation, presentation rubrics, and self-confidence questionnaires. The results showed a significant increase in clarity of delivery, argument structure, and students’ confidence in the experimental group compared to the control group. These findings indicate that public speaking training positively influences the quality of student presentations in the History of Religion course.